The development and validation of an instrument to measure values in mathematics classrooms of matriculation lecturers / Ruzela Tapsir - Ruzela , Tapsir (2017)
The purpose of the study was to develop and validate a self-report instrument which could measure values in mathematics classrooms for matriculation colleges’ lecturers. The universal integrated perspective which is based on faith and belief in God is the basis for the conceptual framework. The ADDIE model which stand for analysis, design, develop, implementation, and evaluate was adapted as the research design. The model is normally used by instructional designers and content developers, in which the implementation stage was dropped in this study. The population of the study consisted of mathematics lecturers from 17 matriculation colleges in the country in which 325 of the lecturers took part. Document analysis protocol was used during the analysis and design phases, clinical interview protocol and survey questions were used for participants in the focus group, survey question was used for the panels of experts, and self-report survey was used for the pilot and the real study. The new self-report instrument consisted of 36 items and used 5-point Likert scale. There were eighteen, eight, and ten values items representing the general education, mathematical education, and mathematics values. Each of this sub construct contained four, two, and three dimensions respectively. Qualitative and quantitative analysis were used during the development stage for content validity and quantitative analysis was used for construct validity during the evaluation stage. The instrument recorded high Cronbach alpha values for the construct and sub-constructs indicating high internal consistencies. Goodness-of-fit indices for the structure of the model indicated that several fit indices values although close, failed to meet commonly accepted standards for the three sub-constructs. Principal component analysis (PCA) of the residuals showed multi-dimensionality for general education values and unidimensional for mathematics education values and values in mathematics. Teaching experience was the only factor contributing towards the score of the mathematics education values and only the pairs of 3-5 with 6-10 and 6-10 with 11-15 were found to have significance mean difference. It was also found that respondents with more teaching experience were inclined towards the the empiricism and universal integrated views of mathematics. The instrument may contribute towards providing more knowledge towards values development in teaching and learning of mathematics subjects.